2021
DOI: 10.3390/agronomy11091787
|View full text |Cite
|
Sign up to set email alerts
|

Ensifer aridi LMR001T Symbiosis and Tolerance to Stress Do Not Require the Alternative Sigma Factor RpoE2

Abstract: The recently proposed species Ensifer aridi represents an interesting model to study adaptive mechanisms explaining its maintenance under stressful pedo-climatic conditions. To get insights into functions associated with hyperosmotic stress adaptation in E. aridi, we first performed RNAseq profiling of cells grown under sub-lethal stresses applied by permeating (NaCl) and non-permeating (PEG8000) solutes that were compared to a transcriptome from unstressed bacteria. Then an a priori approach, consisting of ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(24 citation statements)
references
References 74 publications
(122 reference statements)
3
21
0
Order By: Relevance
“…However, the mutation of the rpoE2 gene suggested that the response was complex and that alternative regulatory mechanisms may be recruited by the bacterium to cope with various stresses. Among genes that were found differentially regulated, a strong repression of motility genes could be identified and validated phenotypically by swimming assays [15]. We also found that salt stress altered regulation for a number of genes involved in the methionine cycle generating S-adenosylmethionine (SAM), the universal methyl donor, in inositol transport and catabolism or in trehalose de novo biosynthesis and transport [15].…”
Section: Introductionmentioning
confidence: 94%
See 4 more Smart Citations
“…However, the mutation of the rpoE2 gene suggested that the response was complex and that alternative regulatory mechanisms may be recruited by the bacterium to cope with various stresses. Among genes that were found differentially regulated, a strong repression of motility genes could be identified and validated phenotypically by swimming assays [15]. We also found that salt stress altered regulation for a number of genes involved in the methionine cycle generating S-adenosylmethionine (SAM), the universal methyl donor, in inositol transport and catabolism or in trehalose de novo biosynthesis and transport [15].…”
Section: Introductionmentioning
confidence: 94%
“…Seeds of Vachellia tortilis subsp. raddiana and endemic Moroccan Vachellia gummifera were surface sterilized, germinated, and cultivated, as described previously [15]. Briefly, after germination (5 days in the dark), young seedlings were transferred in pots containing sterilized sand and Ensifer aridi strains were inoculated using 1 mL of washed cells at an optical density (600 nm) ≈ 0.7 corresponding to exponential growth phase.…”
Section: Phenotypic Characterization Of the Mutants 231 Plant Nodulat...mentioning
confidence: 99%
See 3 more Smart Citations